2019
DOI: 10.1111/eos.12611
|View full text |Cite
|
Sign up to set email alerts
|

Orthodontic treatment need, self‐esteem, and oral health‐related quality of life among 12‐yr‐old schoolchildren

Abstract: The aim of this study was to investigate the association between orthodontic treatment need and oral health‐related quality of life (OHRQoL) among 12‐yr‐old children. The study also assessed whether self‐esteem modifies and/or moderates this relationship. Cross‐sectional data on 406 schoolchildren aged 12 yr were analyzed. Data on socio‐economic and demographic characteristics, dental pain, self‐esteem, and OHRQoL were collected using validated questionnaires. Orthodontic treatment need was assessed, through d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 41 publications
(101 reference statements)
0
10
0
3
Order By: Relevance
“…It is also useful for modeling the count data with many zero-valued observations in the outcome variable (e.g., CPQ sum score) distribution and to overcome the existing over-dispersion problem [49]. In oral health research, these conditions are quite common and, therefore, the NBR is increasingly chosen to overcome the problems [77,78]. In the current study, NBR was found to fit the data well enough and was apparently better than that of the conventional Poisson regression (data were not shown).…”
Section: Discussionmentioning
confidence: 99%
“…It is also useful for modeling the count data with many zero-valued observations in the outcome variable (e.g., CPQ sum score) distribution and to overcome the existing over-dispersion problem [49]. In oral health research, these conditions are quite common and, therefore, the NBR is increasingly chosen to overcome the problems [77,78]. In the current study, NBR was found to fit the data well enough and was apparently better than that of the conventional Poisson regression (data were not shown).…”
Section: Discussionmentioning
confidence: 99%
“…The findings rejected the study hypothesis because, even when the quality of life was evaluated based on the item levels, the anterior occlusal characteristics in the mixed dentition had no impact on the OHRQoL. Previous studies 3,4,7,8,[20][21][22][23][24][25][26][27][28][29] showed that an increased overjet and increased spacing, especially a midline diastema, were the conditions that most affected the individual, regardless of age. Still, the older children become, the more their malocclusion affects their a Values are given as n (%).…”
Section: Discussionmentioning
confidence: 87%
“…The lower is the score, the better is the quality of life. This index is negatively impacted by malocclusions in both adolescents and adults, making sense to begin orthodontic treatment [3].…”
Section: Background and Rationale {6a}mentioning
confidence: 99%